The Improvement of Sepsis-Associated Encephalopathy by P2X7R Inhibitor through Inhibiting the Omi/HtrA2 Apoptotic Signaling Pathway. (27th January 2022) - Wang, Kaifang; Sun, Meiyan; Juan, Zhaodong; Zhang, Jianxin; Sun, Yingui; Wang, Guizhi; Wang, Chunling; Li, Yanjing; Kong, Wenwen; Fan, Lulu; Zhang, Yue; Zhao, Hongxiang; et al.
Abstract : The pathogenesis of sepsis-associated encephalopathy (SAE) involves many aspects, including intracellular peroxidative stress damage, mitochondrial dysfunction, and cell apoptosis. In this study, we mainly explored the influence of P2X7R on the cognitive function of SAE and its molecular mechanism. We established a sepsis model using lipopolysaccharide (LPS) stimulation, followed by an assessment of cognitive function using Morris water maze, and then Western Blot was used to analyze the expression of tight junction proteins ZO-1 and Occludin in the hippocampus of mice. TUNEL assay was used to analyze the apoptosis of brain cells in frozen brain slices of mice during sepsis. Human brain microvascular endothelial cells (HBMECs) were used to research the molecular mechanism of brain cell damage induced by P2X7R. The results showed that P2X7R inhibitors dramatically improved the survival rate of mice, relieved the cognitive dysfunction caused by LPS stimulation, and significantly reduced the brain cell apoptosis caused by LPS. In addition, the inhibition of P2X7R can also reduce the production and accumulation of reactive oxygen species (ROS) in HBMECs in vitro and inhibit the apoptosis signaling pathway associated with mitochondrial serine protease Omi/HtrA2 in HBMECs in vitro. These results suggest that P2X7R has strong value as a potential target for the treatment of SAE.